2019
DOI: 10.1080/08870446.2019.1579911
|View full text |Cite
|
Sign up to set email alerts
|

A randomised trial of the effect of appearance versus health-framed messages on engagement with an online brief screening and alcohol reduction intervention

Abstract: Objectives: To compare the impact of appearance versus healthframed messages on engagement in a brief web-based risk screening and alcohol reduction intervention. Design: Randomised trial delivered via Drinkaware's website. Visitors were exposed to appearance (n ¼ 51,588) or health-framed messages (n ¼ 52,639) directing them towards an AUDIT-C risk screening questionnaire. Users completing this questionnaire were given feedback on their risk level and extended frame-congruent information. Outcomes: The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…While these reasons are accurate (Aune et al 2017;Oyebode et al 2014;Tohill 2005;WHO 2003), the absence of sufficient action by the population suggests that health-based reasons may not be motivating. FV, however, are also beneficial for body-weight, both as energy-dilute foods for those who are overweight (Tohill 2005;WHO 2003) and as often acceptable nutritious foods for those who are underweight (National Institutes of Clinical Excellence 2021), and considerable research demonstrates a value for appearance-oriented strategies for promoting health behaviours (Appleton 2016;Dempster et al 2006;Flett et al 2013;Grogan et al 2011;Jones and Leary 1994;Persson et al 2018;Sallis et al 2019;Smith Kholn and Rogers 1991;Williams et al 2013). Improved attitudes and intentions towards safe sun behaviours, smoking cessation, alcohol reduction, healthy eating and exercise have all been found in response to appearanceoriented interventions (Dempster et al 2006;Flett et al 2013;Grogan et al 2011;Jones and Leary 1994;Persson et al 2018;Sallis et al 2019;Smith Kholn and Rogers 1991;Williams et al 2013), and corresponding behaviours are also found (Flett et al 2013;Persson et al 2018;Sallis et al 2019;Williams et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While these reasons are accurate (Aune et al 2017;Oyebode et al 2014;Tohill 2005;WHO 2003), the absence of sufficient action by the population suggests that health-based reasons may not be motivating. FV, however, are also beneficial for body-weight, both as energy-dilute foods for those who are overweight (Tohill 2005;WHO 2003) and as often acceptable nutritious foods for those who are underweight (National Institutes of Clinical Excellence 2021), and considerable research demonstrates a value for appearance-oriented strategies for promoting health behaviours (Appleton 2016;Dempster et al 2006;Flett et al 2013;Grogan et al 2011;Jones and Leary 1994;Persson et al 2018;Sallis et al 2019;Smith Kholn and Rogers 1991;Williams et al 2013). Improved attitudes and intentions towards safe sun behaviours, smoking cessation, alcohol reduction, healthy eating and exercise have all been found in response to appearanceoriented interventions (Dempster et al 2006;Flett et al 2013;Grogan et al 2011;Jones and Leary 1994;Persson et al 2018;Sallis et al 2019;Smith Kholn and Rogers 1991;Williams et al 2013), and corresponding behaviours are also found (Flett et al 2013;Persson et al 2018;Sallis et al 2019;Williams et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…a message depicting the effect of alcohol on physical appearance) which were then discussed as part of the interviews. Prior research has investigated appearance‐related message themes and found that in comparison with health‐focused message themes, the appearance message resulted in higher likelihood of engaging with a brief alcohol intervention, whereas the health‐focused theme resulted in increased likelihood to seek out further resources (Sallis et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term alcohol usage contributes to alcohol-related brain damage and extensive cognitive impairment ( 15 , 16 ) and those with AUD are also more likely to develop Wernicke–Korsakoff syndrome. These result in diagnostic characteristics such as rapid memory loss, learning disabilities, and amnesic confabulatory syndrome ( 17 ).…”
Section: Introductionmentioning
confidence: 99%